2012
DOI: 10.1002/dev.21083
|View full text |Cite
|
Sign up to set email alerts
|

Precocious hand use preference in reach‐to‐eat behavior versus manual construction in 1‐ to 5‐year‐old children

Abstract: The variation in hand use as a function of task and developmental age poses a problem for understanding how and when "handedness," preferred use of one hand, develops. The present cross-section study is the first to contrast hand preference use for the natural and frequently used reach-to-eat movement with a constructional task that requires a very similar reach-to-grasp movement. Thirty children between the ages of 1 and 3 years completed an eating task, in which they grasped small food items (Cheerios™ or Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 25 publications
6
28
0
Order By: Relevance
“…While it is unlikely that mirror neurons are limited to grasping movements alone, the proximity of mirror neurons to the production site of hand-to-mouth movements may indicate a functional link between the two systems. This may present an explanation for the early development of a right-hand preference for grasp-to-eat actions observed by Sacrey and colleagues, who showed that preference for unimanual self-feeding develops several years earlier than hand preference for grasp-to-manipulate tasks (Sacrey et al 2012a). It is possible to speculate that the mirror neuron system, being important for learning, should be particularly necessary and active during the period of time in which a child first gains control of distal movements (Fagard 2000;Fagard and Marks 2000;Sacrey et al 2012b).…”
Section: Discussionmentioning
confidence: 65%
“…While it is unlikely that mirror neurons are limited to grasping movements alone, the proximity of mirror neurons to the production site of hand-to-mouth movements may indicate a functional link between the two systems. This may present an explanation for the early development of a right-hand preference for grasp-to-eat actions observed by Sacrey and colleagues, who showed that preference for unimanual self-feeding develops several years earlier than hand preference for grasp-to-manipulate tasks (Sacrey et al 2012a). It is possible to speculate that the mirror neuron system, being important for learning, should be particularly necessary and active during the period of time in which a child first gains control of distal movements (Fagard 2000;Fagard and Marks 2000;Sacrey et al 2012b).…”
Section: Discussionmentioning
confidence: 65%
“…The good news is that these techniques are relatively simple and inexpensive, and can be used with minimal instruction for participants of many ages and abilities. For example, some preliminary work (Sacrey, Arnold, Whishaw & Gonzalez, 2013) suggests that a right hand grasping bias emerges at the age of 4 or 5 years, although this particular study employed only ten right handed children in each age group, so further research is needed to firm up this intriguing conclusion (which could easily be contrasted with other milestones of behavioural asymmetry; Gentry & Gabbard, 1995;Scharoun & Bryden, 2014). …”
Section: Discussionmentioning
confidence: 95%
“…Tests of normality (Kolmogorov-Smirnov & ShapiroWilk) revealed that the data was normally distributed. An analysis of variance (ANOVA) was performed on the values of right-hand use, as in previous reports using similar tasks and measures (Bryden & Huszczynski, 2011;Bryden, Pryde & Roy, 2000;Cavill & Bryden, 2003;de Bruin, Bryant & Gonzalez, 2014;Sacrey, Arnold, Whishaw & Gonzalez, 2013;Stone & Gonzalez, 2014a,b;Stone et al, 2013).…”
Section: Discussionmentioning
confidence: 99%